Feasibility of semen collection in red-winged tinamou (Rhynchotus rufescens) by manual stimulation and sazonality implications - Paranzini, Cristiane Sella [UNESP]; Correia, Luiz Eduardo Cruz dos Santos [UNESP]; de Camargo, Laiza Sartori [UNESP]; Silva, Kelry Mayara [UNESP]; de França, Tatyana Mendes [UNESP]; Silva, Josineudson Augusto de Vasconcelos [UNESP]; Veiga, Nabor [UNESP]; de Souza, Fabiana Ferreira [UNESP] (Elsevier, 2018)
This study aimed to report in detail, the technique and challenges of cloacal massage, to collect and evaluate semen from red-winged tinamou (Rhynchotus rufescens) keep in captivity, performed by only one technician. Sixty-four semen collection attempts, from 16 adult males, during breeding season and 16 attempts form these same 16 males in non-breeding season, were performed. Prior to collection, all animals were conditioned to cloacal massage for 6 weeks and the ejaculates were succeed with viable spermatozoa and then, evaluated for feces, urine and mucus contamination, volume, concentration, sperm vigor, motility, morphological defects and acrosome integrity. Semen collection success rate was 63% in breeding season and 2 (5%) samples were discarded by grade 5 contamination. Only 3 ejaculates from 16 tinamou were obtained in non-breeding season. Sperm concentration and acrosome integrity was higher (p = 0.00) in breeding season, and the percentage of total sperm morphological defects, were high in both in breeding and out breeding season. Overall, we concluded that the red-winged tinamou breeding season, is linked to photoperiod (spring and summer), and at this period time, semen can be obtained by cloacal massage collection satisfactorily, allowing its use in reproduction biotechnologies and sperm cryopreservation.
Keywords: Bird; Season; Semen collection; Sperm quality; Tinamidae